The Evolution of Children’s Literature - Khadka, Kul Bahadur (Journal of Development Review, 2020)
Children’s literature is literature for children and about children, maybe written by children or adult writers. The article sheds lights on the meaning and importance of children’s literature. It mainly focuses on how children’s literature in general has been evolving in the English and Nepali contexts of literary history. Some writers and their books have been consulted and some critics’ opinions have been cited in order to find out the general trends of the evolution of children’s literature. Efforts have been made to observe some commonalties and contrasts in the evolution trends between children’s literature, mainly in English, and children’s literature in Nepal. It is observed that the sources and themes of children’s literature are similar both in English and Nepali. The oral trend of sharing folk and mythic stories is also similar in both cases. Writing books that can be leveled as children’s literature started very late in Nepal, however the story-telling tradition in village houses by grandparents, parents and uncles is very old.